The Public Procurement and Government Spending as Implementation of New Public Management - Haryanto Haryanto (Universitas Swadaya Gunung Jati, 2023)
AbstractThis study examines the effect of competition in the public procurement of goods and services on government spending. Using the competitive bidding model, this study examines the impact of competition on the number of participants, the bidder's net assets (financial ability), distance, and project size on government spending. The research sample used purposive sampling. Hypothesis testing using multiple linear regression analysis. The results of this study prove that the variables of the number of bidders, net assets, and project size affects government spending. However, the distance variable does not affect government spending. This study also proves that these variables simultaneously affect government spending.Keywords: Competitive bidding; Government spending; Public procurement. AbstrakPenelitian ini bertujuan untuk menguji pengaruh persaingan dalam pengadaan barang dan jasa publik terhadap belanja pemerintah. Dengan menggunakan model penawaran kompetitif, penelitian ini mengkaji dampak persaingan terhadap jumlah peserta, aset bersih penawar (kemampuan finansial), jarak, dan ukuran proyek terhadap belanja pemerintah. Sampel penelitian menggunakan purposive sampling. Pengujian hipotesis menggunakan analisis regresi linier berganda. Hasil penelitian ini membuktikan bahwa variabel jumlah penawar, aset bersih, dan ukuran proyek berpengaruh terhadap belanja pemerintah. Namun, variabel jarak tidak mempengaruhi pengeluaran pemerintah. Penelitian ini juga membuktikan bahwa variabel-variabel tersebut secara simultan mempengaruhi pengeluaran pemerintah.Kata Kunci: Belanja pemerintah; Penawaran kompetitif; Pengadaan publik.